2003
DOI: 10.1128/jb.185.9.2867-2878.2003
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciensVirB6 Protein Participates in Formation of VirB7 and VirB9 Complexes Required for Type IV Secretion

Abstract: This study characterized the contribution of Agrobacterium tumefaciens VirB6, a polytopic inner membrane protein, to the formation of outer membrane VirB7 lipoprotein and VirB9 protein multimers required for type IV secretion. VirB7 assembles as a disulfide cross-linked homodimer that associates with the T pilus and a VirB7-VirB9 heterodimer that stabilizes other VirB proteins during biogenesis of the secretion machine. Two presumptive VirB protein complexes, composed of VirB6, VirB7, and VirB9 and of VirB7, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 50 publications
6
134
1
2
Order By: Relevance
“…Further investigations exploring these stabilizing effects, as well as recent cell biology studies, have led to the development of a biogenesis pathway for this transfer apparatus 22,53 .A crucial intermediate in this pathway is a 'core' structure that is composed of VirB4, VirB7-VirB10 and, probably, VirB6. The existence of this structure is now supported by data from dihybrid screens and complementary biochemical assays [54][55][56][57][58][59] (Table 2). Additionally, some of the interactions required for assembly of the putative core are conserved in the B. pertussis Ptl system.…”
Section: The Transenvelope Mpf Structurementioning
confidence: 80%
See 1 more Smart Citation
“…Further investigations exploring these stabilizing effects, as well as recent cell biology studies, have led to the development of a biogenesis pathway for this transfer apparatus 22,53 .A crucial intermediate in this pathway is a 'core' structure that is composed of VirB4, VirB7-VirB10 and, probably, VirB6. The existence of this structure is now supported by data from dihybrid screens and complementary biochemical assays [54][55][56][57][58][59] (Table 2). Additionally, some of the interactions required for assembly of the putative core are conserved in the B. pertussis Ptl system.…”
Section: The Transenvelope Mpf Structurementioning
confidence: 80%
“…Intriguingly however, recent studies have identified mutations in the VirB11 and VirB6 subunits that 'uncouple' pilus biogenesis from substrate transfer. Some mutations do not affect assembly of a wild-type pilus, but block substrate transfer, whereas, conversely, others prevent pilus formation without affecting substrate transfer 59,69 . So, the formation of a conjugative pilus extending from the cell surface is not, in fact, an obligatory feature of conjugation machines of Gram-negative bacteria.…”
Section: Extracellular Filamentsmentioning
confidence: 98%
“…These data on A. tumefaciens VirB6 clearly demonstrate the importance of VirB6 as a central channel component engaged in a series of substrate-and Mpf-component interactions. The requirement of VirB6 for the stability or functionality of the minor pilus components VirB5 and VirB7 indicates that VirB6 may play an important role in pilus biogenesis or pilus elongation (Hapfelmeier et al, 2000;Jakubowski et al, 2003;Krall et al, 2002). The identiWcation of VirB6 insertion mutants that are deWcient in pilus production (Pil ¡ ) but proWcient in substrate transfer (Tra + ) (Jakubowski et al, 2003) lends further support to this suggestion.…”
Section: Virb6: a Modulator Of The Secretion Channel?mentioning
confidence: 80%
“…The requirement of VirB6 for the stability or functionality of the minor pilus components VirB5 and VirB7 indicates that VirB6 may play an important role in pilus biogenesis or pilus elongation (Hapfelmeier et al, 2000;Jakubowski et al, 2003;Krall et al, 2002). The identiWcation of VirB6 insertion mutants that are deWcient in pilus production (Pil ¡ ) but proWcient in substrate transfer (Tra + ) (Jakubowski et al, 2003) lends further support to this suggestion. The Pil ¡ /Tra + phenotype has only been observed in mutants of the pilin (VirB2) and in mutants of VirB6 and VirB11, but not in mutants of any other Mpf/CP component (Jakubowski et al, 2003;Sagulenko et al, 2001a).…”
Section: Virb6: a Modulator Of The Secretion Channel?mentioning
confidence: 80%
See 1 more Smart Citation